Urgency of Revision of Law Number 7 Year 2017 Regarding Elections in Relation to Money Politics (Law Research Review Quarterly, 2018)
Money politics occurs in almost every election at all levels of the public both at the central and regional levels. The weak regulation (Law No. 7 of 2017) regarding elections is not strong enough to overcome money politics and impose sanctions on money politics compared to Law No. 10 of 2016 concerning the election which was also reinforced by the Election Supervisory Body Regulation No. 13 of 2016 concerning procedures for handling administrative violations related to the prohibition of giving and / or promising money or other material that is carried out in a systematic, massive manner in the election of Governors, Regents and Mayors. Besides the problem also with law enforcement itself. This problem itself has become a culture in Indonesian society. This activity (money politics) does not only threaten clean and effective governance but also clean and honest elections. Those who spend money politics to win elections are usually expected to recover after choosing their investment profitably. If unchecked, the defense of public interest and what is common in retreats. This is a crime, and greatly damages the integrity of elections. We need the legislature to pay attention to how to enforce control over money politics.